PENERAPAN PRINSIP 12 BENAR DALAM PEMBERIAN OBAT: STUDI FENOMENOLOGI PENGALAMAN PRAKTEK KLINIS MAHASISWA KEPERAWATAN DI UNIVERSITAS A - Alexander, Dearly Gabriela; Tambunan, Evelyn Hemme (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Background: Every nursing student will of course undergo clinical practice in their education process. One of the demands in clinical practice is that applying the 12 correct principles in medication administration can prevent errors in administering medication and maintain the professionalism of nurses. However, there are still many students who have not applied the 12 principles of correct medication administration so the risk of errors in medication administration is greater. Objective: The aim of this research is to explain how the clinical practice experiences of Indonesian Adventist University nursing students in applying the 12 principles of correct medication administration. Method: This research is a qualitative research with a phenomenological study of students' experiences in applying the 12 correct principles of medication administration when carrying out clinical practice. Research data was collected through focused discussions consisting of 2 groups consisting of 8 UNAI nursing students each who were selected using convenience sampling, where the students involved are nursing students who have participated in clinical practice at least twice. Research data stored in recorded form will then be transcribed and grouped into appropriate themes. Results: From this research, research results were obtained in the form of students' experiences of making mistakes, the challenges faced by students, the benefits of applying the 12 correct principles and how students overcome the challenges they experience. Conclusion: The application of the 12 correct principles in the clinical practice of UNAI nursing students helps students develop skills and knowledge and increases the self-confidence of UNAI nursing students. Suggestion: Future researchers are expected to be able to research more deeply into students' clinical practice experiences, especially in applying the 12 correct principles of drug administration with a more specific scope.